Formulasi Tablet Kunyah Asetosal Dengan Variasi Konsentrasi Gelatin Sebagai Bahan Pengikat Terhadap Uji Fisik Tablet - Kinanthi Dwi Utami; Rani Prabandari; Sunarti (Jurnal Farmasi IKIFA, 2023)
Acetosal, a nonsteroidal anti-inflammatory drug that is included in the category of drugs with a dose of 80 mg. In patients with coronary heart disease and severe hypertension, this drug is used as antiplatelet therapy with the aim of preventing stroke. Acetosals are included in the BCS class II category, so efforts are needed to develop formulations that can increase the speed of dissolution and provide a fast effect. This study aims to determine the variation in gelatin concentration as a binding agent to physical properties and determine the best gelatin concentration that meets the dissolution test of acetosal chewable tablets. The method used to make acetosal chewable tablets is direct felt. Acetosal chewable tablets are made into 3 formulas with variations in the concentration of gelatin binders of 2%, 6%, and 10%. The data obtained is then analyzed with one-way ANOVA. The results showed variations in gelatin concentrations of 2%, 6%, and 10% resulting in good physical properties of acetosal chewable tablets. The gelatin concentration of 2% in formula 1 showed the best results with an average test value of uniformity of weight 220.6 ± 1.42 mg, uniformity of diameter size 0.838 ± 0.01 cm, and thickness 0.436 ± 0.01 cm, hardness 4.3 ±0.15 kg, brittleness 0.49 ± 0.32%, crushing time 31 ± 3.0 seconds and dissolution 95.81%. A significant difference in values was found in the hardness test results (p = 0.001) and the time of destruction (p = 0.000). The best percent dissolution is found in Formula 1 with a dissolution value of 95.81%.